The Implementation of the Next Generation Science Standards and the Tumultuous Fight to Implement Climate Change Awareness in Science Curricula - Christopher Thomas Holland (Brock Education: a Journal of Educational Research and Practice, 2020)
The following article examines the implementation and controversy that surround climate change education and the implementation of the Next Generation Science Standards (NGSS). In order to fully understand why NGSS and climate change education continue to generate significant public debate, one must examine the work of both climate advocates and detractors. Therefore, this paper first examines the manner in which climate change continues to remain a debatable topic of discussion throughout American classrooms despite overwhelming scientific consensus. After, it explores how the debate over climate change stems from differing ethical cornerstones. Moreover, it delves into the oppositional perspective on climate change implementation by exploring the work of Truth in Texas Textbooks (TTT). Subsequently, it introduces and analyzes the creation and implementation of NGSS and discusses how adoption of NGSS and stronger levels of opposition to TTT is responsive policy that remains a necessary step to challenging global issues created by climate change.